Education plays an important rol The Influence of Family and School Religiosity on Students' Religious Intelligence in Senior High Schools and Islamic Senior High Schools - Nur Adhibatun Muthmainah; Munawar Rahmat; Agus Fakhruddin (Khazanah Pendidikan Islam, 2025)
This study aims to explore the influence of family religiosity and educational institutions on students' religious intelligence, with a particular focus on comparing students from Madrasah Aliyah and public high schools. In light of the decline in religious values among Indonesian youth amidst globalization and secularization, the study seeks to understand how family and school environments contribute to the development of religious intelligence and how substantive religiosity, encompassing faith, worship, and moral values, plays a role in shaping students’ spiritual and moral development. A quantitative correlational design was employed, with data collected from 400 grade XI students across two schools: SMAN 24 and MAN 2 in East Bandung. A 4-point Likert scale questionnaire was used to measure family religiosity, school religiosity, and substantive religiosity. Spearman correlation tests were conducted to examine relationships between the variables, while the Mann-Whitney U test was used to compare religious intelligence between Madrasah Aliyah and public school students. The study found a significant positive correlation between family religiosity and religious intelligence, with parental involvement being the most influential factor. Madrasah Aliyah students showed higher religious intelligence than public school students, attributed to the integrated religious curriculum and daily religious practices in madrasahs. Additionally, substantive religiosity, which includes faith, worship, and morals, significantly enhances religious intelligence, highlighting the importance of a holistic approach to religious education. The findings suggest that a synergistic approach between family and school is essential for fostering religious intelligence. Public schools should consider integrating more spiritual practices into their curricula. This research also emphasizes the need for educational policies that incorporate both cognitive and spiritual learning to nurture well-rounded, spiritually intelligent students. This study introduces a quantitative comparison of the influences of family and school religiosity, contributing new insights into how substantive religiosity shapes religious intelligence in Indonesian youth.